Obstacles to Optimal Antenatal Corticosteroid Administration to Eligible Patients - Rood, Kara M.; Ugwu, Lynda G.; Grobman, William A.; Bailit, Jennifer L.; Wapner, Ronald J.; Varner, Michael W.; Thorp, John M., Jr.; Caritis, Steve N.; Tita, Alan T. N.; Saade, George R.; Rouse, Dwight J.; Blackwell, Sean C.; Tolosa, Jorge E.; for the Eunice Kennedy Shriver National Institute of Child Health Human Development Maternal-Fetal Medicine Units (MFMU) Network (American Journal of Perinatology, 2022)
Objective Administration of antenatal corticosteroids (ANCS) is recommended for individuals expected to deliver between 24 and 34 weeks of gestation. Properly timed administration of ANCS achieves maximal benefit. However, more than 50% of individuals receive ANCS outside the recommended window. This study aimed to examine maternal and hospital factors associated with suboptimal receipt of ANCS among individuals who deliver between 24 and 34 weeks of gestation.Study Design Secondary analysis of the Assessment of Perinatal Excellence (APEX), an observational study of births to 115,502 individuals at 25 hospitals in the United States from March 2008 to February 2011, was conducted. Data from 3,123 individuals who gave birth to a nonanomalous live-born infant between 240/7 to 340/7 weeks of gestation, had prenatal records available at delivery, and data available on the timing of ANCS use were included in this analysis. Eligible individuals' ANCS status was categorized as optimal (full course completed >24 hours after ANCS but not >7 days before birth) or suboptimal (none, too late, or too early). Maternal and hospital-level variables were compared using optimal as the referent group. Hierarchical multinomial logistic regression models, with site as a random effect, were used to identify maternal and hospital-level characteristics associated with optimal ANCS use.Results Overall, 83.6% (2,612/3,123) of eligible individuals received any treatment: 1,216 (38.9%) optimal and 1,907 (61.1%) suboptimal. Within suboptimal group, 495 (15.9%) received ANCS too late, 901 (28.9%) too early, and 511 (16.4%) did not receive any ANCS. Optimal ANCS varied depending on indication for hospital admission (p < 0.001). Individuals who were admitted with intent to deliver were less likely to receive optimal ANCS while individuals admitted for hypertensive diseases of pregnancy were most likely to receive optimal ANCS (10 vs. 35%). The median gestational age of individuals who received optimal ANCS was 31.0 weeks. Adjusting for hospital factors, hospitals with electronic medical records and who receive transfers have fewer eligible individuals who did not receive ANCS. ANCS administration and timing varied substantially by hospital, optimal frequencies ranged from 9.1 to 51.3%, and none frequencies from 6.1 to 61.8%. When evaluating variation by hospital site, models with maternal and hospital factors did not explain any of the variation in ANCS use.Conclusion Optimal ANCS use varied by maternal and hospital factors and by hospital site, indicating opportunities for improvement.Key Points
Keywords: antenatal corticosteroids; preterm birth; preterm delivery